Habib dalam Pemaknaan Generasi Milenial eks-Simpatisan Front Pembela Islam Pasuruan - Jafar, Jafar (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
This study focuses on the meaning of the millennial generation who are former FPI Pasuruan sympathizers on the meaning of habib. This research is motivated by habib's position as a charismatic figure. They occupy a central role, because they are placed as